2013
DOI: 10.1097/sap.0b013e31826eab9e
|View full text |Cite
|
Sign up to set email alerts
|

Application of Topical Negative Pressure (Vacuum-Assisted Closure) to Split-Thickness Skin Grafts

Abstract: Topical negative pressure increases quantity and quality of split skin graft take compared to traditional bolster dressings. The advantages are increased in irregularly contoured, technically difficult wounds and suboptimal recipient wound beds where it seems to be the best modality currently available. Large-scale randomized clinical controlled trials remain scanty in all areas of wound dressing research including negative pressure therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 31 publications
4
59
0
6
Order By: Relevance
“…Nevertheless, split-skin take was rather high when using TNP. These findings are in accordance with the outcome in nondiabetic burn patients 12,13 and may be explained by the reduction of hematoma and seroma and better graft fixation on the wound bed with reduced shear stress. 19 Different factors can delay the wound healing process.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, split-skin take was rather high when using TNP. These findings are in accordance with the outcome in nondiabetic burn patients 12,13 and may be explained by the reduction of hematoma and seroma and better graft fixation on the wound bed with reduced shear stress. 19 Different factors can delay the wound healing process.…”
Section: Discussionsupporting
confidence: 91%
“…8,9,11 It is known that topical negative pressure (TNP) dressings alias negative pressure wound therapy can increase graft take rate, even in burned patients. 12,13 However, the effectiveness of TNP on grafts in diabetic patients with foot scalds has never been reported. Therefore, we compared the outcome of antiseptic dressing with a circular TNP dressing on the freshly laid split-thickness skin graft (SSG) after tangential excision in insulin-dependent diabetes mellitus (IDDM) patients after deep dermal scald of the foot (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 98%
“…In agreement with the recommendations of Azzopardi et al 68 , the highest recommendations of the NPWT-EP were related to split-thickness skin-graft procedures and indicated that NPWT must be considered to improve splitthickness skin-graft success (quality of evidence, grade A), should be considered in high-risk patients or wounds (quality of evidence, grade B), and should be left undisturbed for three to seven days on continuous pressure (quality of evidence, grade B).…”
Section: Levels Of Evidence and Recommendationssupporting
confidence: 90%
“…Azzopardi et al 68 , in their evidencebased literature review from the past decade, made three recommendations. First, NPWT application to splitthickness skin grafts may promote blood flow at the graft bed and surrounding wound while stimulating angiogenesis and basement membrane integrity (quality of evidence, grade C).…”
Section: Management Of Skin Grafts and Flapsmentioning
confidence: 98%
“…Following reconstructive surgery with a caudal sartorius myocutaneous flap, VAC therapy was applied at 50 mmHg. Although some authors make recommendations that subatmospheric pressure settings of only 50 mmHg are needed to reduce edema over closed incisions or skin grafts, clinical cases report a 95% success rate with split thickness skin grafting and adjunctive negative pressures between 75 and 125 mmHg [7,[21][22][23]. The negative pressure setting of 50 mmHg was chosen based on clinical experience with skin grafts treated adjunctively with VAC therapy at our institute.…”
Section: Discussionmentioning
confidence: 99%